Universities and Government in Post-War Japan - Yamamoto, Shinichi (Canadian Journal of Higher Education, 2004)
Japan's higher education system, in which private universities and colleges play an important part, has embarked on far-reaching reform in the 1990s. Its main objective was to free the national (public) universities from tight control by the central government and to give them more autonomy. In light of dramatic demographic changes, especially a much smaller proportion of people of traditional university age, and considering that higher education research was not useful to Japanese industry, the status and management of public universities have been transformed to allow more autonomy, competition, and private sector-style management. Meanwhile, mechanisms have been introduced to hold the newly independent universities more accountable.